How, When, Where, to Whom Tell about Sexual Abuse? Forms of the Delay in ¿Por qué volvías cada verano? By Belén López Peiró (2022)
¿Por qué volvías cada verano? by Argentinean writer Belén López Peiró is analysed in this paper from the discursive forms, her own literary project, and the issue of narrating the sexual abuse lately. The analysis is carried out from a feminist perspective that proposes to dismantle heteronormative readings of sexual abuse. This book is inserted in a corpus of novels which allowed to analyse continuities and ruptures in the narration of violence. The book works as an expanded archive involving an experiential writing with a village's story, a sheriff’s story, and the unsuccessful trial on a case of domestic sexual abuse. This book also works as a political point of view in the socio-cultural Argentinean context. A personal story in this novel embodies values and overcomes from the private to the public.